Hepatitis E virus infection as a promoting factor for hepatocellular carcinoma in Cameroon: Preliminary Observations. (November 2017) - Amougou Atsama, Marie; Atangana, Paul Jean Adrien; Noah Noah, Dominique; Moundipa, Paul Fewou; Pineau, Pascal; Njouom, Richard
Abstract: Objectives: To determine the seroprevalence of hepatitis E virus (HEV) infection in patients with chronic hepatitis and/or hepatocellular carcinoma (HCC) and to assess its potential consequences for disease progression. Methods: We conducted a prospective case-control study on patients with HCC hepatitis B or C related and non-HCC patients including patients with CLD and patients without clinical evidence of liver disease. Anti-HEV IgG and IgM were tested by ELISA using commercially available kits. Liver damage was assessed by alanine aminotransferase, aspartate aminotransferase, platelets and prothrombin measurements. Results: We observed a significant anti-HEV IgG carriage in HCC patients compared to non-HCC subjects with CLD (41.8% vs 12.6%; P = 9.1 E-6; OR = 4.8, 95%CI: 2.3-10.6). HCC patients with HEV infection display more profound alterations of circulating liver enzymes, platelets count and prothrombin time than HCC patients without sero-reactivity to HEV. Conclusion: Overall, this study indicates a high prevalence of HEV infection in Cameroonian patients with CLD and HCC. These data suggest either that patients with liver tumors are more susceptible to hepeviral infection or that, in a tropical context, HEV might promote the progression of liver diseases towards tumor.